Kasai Hepatoportoenterostomy for Biliary Atresia in Children: Technical Notes and Details of Perioperative Therapy - Boscarelli, Alessandro (International Journal of Pediatrics and Child Health, 2019)
Biliary atresia is a progressive obliterative cholangiopathy of neonates, which causes jaundice and can lead to end stage liver disease. Despite recent improvements, Kasai hepatoportoenterostomy remains the standard surgical procedure to re-establish bile flow in these patients to date. Nevertheless, the majority of children with biliary atresia ultimately undergo liver transplantation. Herein, technical notes and perioperative therapies in children undergoing Kasai operation are reported.